Conservation genetics of the giant otter (Pteronura brasiliensis (Zimmerman, 1780)) (Carnivora, Mustelidae) - Garcia,DM. (2007)
The giant otter (Pteronura brasiliensis) is an aquatic mammal of the Mustelidae family, endemic to South America. Its original distribution corresponds to the region from the Guyanas to Central-North Argentina, but it is extinct or on the verge of extinction in most of its historical range. Currently, the species is considered endangered by the World Conservation Union (IUCN). Based on its geographic distribution in the South American continent and on some morphological characters, two subspecies were suggested: P. brasiliensis brasiliensis, occurring in the Amazon and Orinoco River Basins, and P. brasiliensis paranensis, in the Paraná and Paraguai River Basins. However, there is no consensus on assuming this subspecies division and no detailed studies have been carried out to elucidate this question. This study aims to evaluate the genetic diversity and population structure of Pteronura brasiliensis along its range in Brazil to check the possibility of the existence of two distinct subspecies using also a reciprocal monophyly criterion. We analyzed the control region, and the Cytochrome b and Cytochrome c Oxidase subunit I genes of the mitochondrial DNA in several giant otter populations from the Amazon and Paraguai River Basins. Analyses have indicated some degree of geographic correlation and a high level of inter-population divergence, although the subspecies division is not highly supported. As we observed strong population structure, we cannot rule out the existence of further divisions shaping the species distribution. The results suggest that a more complex population structure occurs in P. brasiliensis, and the conservation practice should concentrate on preserving all remaining local populations.